Dislocation Mobilities in GaN from Molecular Dynamics Simulations. Issue 1741 (2nd February 2015) - Weingarten, N. Scott
ABSTRACT: The results of molecular dynamics (MD) simulations of dislocation glide in GaN using a Tersoff potential are presented. The simulation methodology involves applying a constant shear stress to a single crystal system containing an individual dislocation, with multiple slip systems considered. Upon reaching a steady state, the dislocation velocity as a function of applied stress and temperature are determined. Edge dislocations with a -type Burgers vectors in the basal, prismatic and pyramidal planes have been analyzed over the temperature range of 300-1300K. The results from simulations of c -type edge dislocations at 1300 K are also presented.